Disparities in virtual cardiology visits among Veterans Health Administration patients during the COVID-19 pandemic. Issue 4 (15th December 2022) - Tisdale, Rebecca L; Ferguson, Jacqueline; Van Campen, James; Greene, Liberty; Sandhu, Alexander T; Heidenreich, Paul A; Zulman, Donna M
Abstract: Objective: In response to the coronavirus disease 2019 (COVID-19) pandemic, the Veterans Health Administration (VA) rapidly expanded virtual care (defined as care delivered by video and phone), raising concerns about technology access disparities (ie, the digital divide). Virtual care was somewhat established in primary care and mental health care prepandemic, but video telehealth implementation was new for most subspecialties, including cardiology. We sought to identify patient characteristics of virtual and video-based care users in VA cardiology clinics nationally during the first year of the COVID-19 pandemic. Materials and Methods: Cohort study of Veteran patients across all VA facilities with a cardiology visit January 1, 2019–March 10, 2020, with follow-up January 1, 2019–March 10, 2021. Main measures included cardiology visits by visit type and likelihood of receiving cardiology-related virtual care, calculated with a repeated event survival model. Results: 416 587 Veterans with 1 689 595 total cardiology visits were analyzed; average patient age was 69.6 years and 4.3% were female. Virtual cardiology care expanded dramatically early in the COVID-19 pandemic from 5% to 70% of encounters. Older, lower-income, and rural-dwelling Veterans and those experiencing homelessness were less likely to use video care (adjusted hazard ratio for ages 75 and older 0.80, 95% confidence interval (CI) 0.75–0.86; for highly rural residents 0.77, 95% CI 0.68–0.87; for low-income status 0.94, 95% CI 0.89–0.98; for homeless Veterans 0.85, 95% CI 0.80–0.92). Conclusion: The pandemic worsened the digital divide for cardiology care for many vulnerable patients to the extent that video visits represent added value over phone visits. Targeted interventions may be necessary for equity in COVID-19-era access to virtual cardiology care. Lay Summary: Virtual cardiology care in the Veterans Health Administration expanded dramatically early in the coronavirus disease 2019 (COVID-19) pandemic from 10% to 70% of encounters, partially compensating for a large and persistent drop in in-person encounters. Several groups with limited healthcare access or high social need were less likely to use video care in particular, including older, lower-income, and rural-dwelling Veterans and those experiencing homelessness. Tailored interventions may be necessary to address this digital divide in COVID-19-era access to virtual cardiology care.